Lectin-positive Spherical Deposits (SPD) in Molecular Layer of Hippocampal Dentate Gyrus of Dementia, Down’s Syndrome, and Schizophrenia: Mini Review - Keiko Ikemoto; Akiyoshi Nishimura (Recent Developments in Medicine and Medical Research Vol. 8, 2021)
Lectins are proteins which specifically bind (or crosslink) carbohydrates. Recent studies have shown the importance of glycosylation in pathogenesis of diseases. We detected lectin-positive spherical deposits (SPD), 3-10 micron in diameter, in the molecular layer of dentate gyrus of hippocampus in dementia, Down’ s syndrome, and schizophrenia. The present study is aimed at elucidating the nature and significances of SPD in etiology of neuropsychiatric illnesses. In schizophrenia, SPD was observed without exception, regardless of having history of pharmacotherapy. By using multi-labeling histochemical methods, single strand DNA was co-localized in hippocampal SPD of schizophrenia with lectin, including GSI-B4 for galactose, and UEA-I for fucose, suggesting that SPD formation in schizophrenia is related to apoptotic processes. The molecular basis of SPD formation should further be investigated in brains with neuropsychiatric illnesses.